Population dynamics and feeding habits of tropical shads Tenualosa spp. in the coastal waters of Sarawak, Malaysia - Mohd Zain, Nur Azrie (2019)
The population dynamics parameters (Asymptotic length, growth coefficient, mortality, recruitment and exploitation), maximum sustainable yield (MSY) and diet compositions of Tenualosa macrura and Tenualosa toli were investigated in the coastal waters of Sarawak. Samples of T. macrura and T. toli were collected between May 2016 and October 2017 from the five different stations which were Sadong, Sebuyau, Daro, Lingga and Mukah in the coastal waters of Sarawak. Relative growth coefficient (b) was 2.942 and 3.408 for males and females of T. macrura, while 2.909 and 3.178 for males and females of T. toli. The negative allometric growth was in males and positive allometric growth was in females for the both species of T. macrura and T. toli. Length and weight relationships were significant (p < 0.05) for the both species with the coefficient of determination (R2) ranging from 0.85 to 0.97. The asymptotic length (L∞) values were estimated as 43.58 cm and 53.03 cm for the T. macrura and T. toli, respectively. The K-scan technique revealed that K values were 0.47 yr-1 for T. macrura and 0.43 yr-1 for T. toli, respectively. Fishing mortality (F) of T. macrura was found to be 2.38 yr-1, while it was 1.88 yr-1 for T. toli. The estimated natural mortality (M) was 0.97 yr-1 and 0.87 yr-1 for T. macrura and T. toli, respectively. The recruitment pattern was continuous, displaying a one major peak event per year for the both species in the investigated area. Exploitation level (E) was estimated as 0.70 and 0.68 for T. macrura and T. toli respectively. Therefore, over exploitation (E > 0.50) might be confirmed for the both species in the coastal waters of Sarawak. It is also revealed that the current fishing pressure was 40% higher for T. macrura and it was 36% higher for T. toli in the investigated area. Therefore, it is necessary to reduce the fishing presure on tropical shads by 40% to get the maximum sustainable yield (MSY). There were nine type of prey items found in the stomach of T. macrura and T. toli, which were phytoplankton, copepod, eggs, shrimp, mollusc, plant materials, worm, debris and unidentified items. Phytoplankton was the dominant prey items for T. macrura and T. toli in percent simple resultant index (%Rs) that was 56.83% and 31.89 %, respectively. Subsequently, %Rs values of T. macrura and T. toli were 9.91% and 21.33% for copepod, 8.28% and 12.04% for eggs, 9.36% and 7.08% for plant materials, 5.97% and 4.9% for mollusc, 5.13% and 0.99% for shrimp. 2.47% and 6.05% for debris, 1.14% and 7.7% for worms, 0.91% and 8.02% for unidentified items, respectively. There was 60% similarity of prey items between T. macrura and T. toli in different months. Whereas, the similarity of the diet composition in T. macrura was 80% in the different months. Among the 9 items of diet composition, 3 items (phytoplankton, plant materials and worms) were dominant and common in the different months of both species. It was concluded that plankton (phytoplankton and copepod) was more than 50% in the diet composition of both T. macrura and T. toli. Therefore, both species in the study areas are exclusively planktivorous.